Menguak Potensi Hasil Perikanan Dalam Mengentaskan Kemiskinan Masyarakat Nelayan Melalui Pemberdayaan Ekonomi Kerakyatan di Kota Sibolga - Asrizal Efendy Nasution (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Poverty is a living condition that is in shortage experienced by a person or household, so as not being able to meet the minimum or decent needs in his life. Populist economy is a family-based economic system, people's sovereignty, and shows a genuine interest in people's economy. This study aims to determine how the potential of fishery in poverty eradication of fishermen community through the empowerment of the populist economy in the city of Sibolga. The method used is library research. The data used are secondary data taken from the BPS Sibolga city. From the results of the discussion can be concluded that the potential of fishery products is quite large and even the second largest contributor after the big trade and retail of 17 indicators of GRDP according to existing business fields in the city of Sibolga was not able to alleviate the poverty of fishermen community. This is because not yet maximizing the economic empowerment of people in the field of fisheries. To that end, the government needs to be more serious in improving the empowerment of the populist economy in the field of fisheries is one of them is the provision of capital and technology assistance that can increase the productivity of fishing communities so that income increases and able to raise the degree out of the strata of poverty. Intensive facilitation and direction also needs to be made in the use of capital and technology assistance provided for the purpose of poverty alleviation through economic empowerment of this person can be achieved.